Queer : "despised sexuality", law, and social change - Narrain, Arvind (Books for Change, 2004)
The last decade of the 20th century in India has seen the emergence of another form of political assertion centring on the hitherto private realm of sexuality. We are increasingly witness to people asserting their right to be different as sexual beings, either in terms of sexual orientation or gender identity. The traditional definitions of activist politics is being forced to engage with new political concerns articulated by people who claim gay, lesbian, hijra, transgender, kothi and numerous other identities. What is common to these identities apart from their roots in sexuality is the fact that they question the heteronormative ideal that the only way in which two human beings can relate romantically, sexually and emotionally is within a heterosexual context.